A systematic review of HER2 blockade for the curative treatment of gastroesophageal adenocarcinoma: Successes achieved and opportunities ahead. (September 2021) - Stroes, Charlotte I.; van den Ende, Tom; Derks, Sarah; van Laarhoven, Hanneke W.M.
Highlights: There is limited additional toxicity of the addition of HER2 targeting agents. Targeting HER2 shows promising results in HER2 positive curatively-treated GEA. Single-agent HER2 targeting seems not sufficient to improve response in curative treatment of GEA. Dual-agent HER2 inhibition could improve response by overcoming treatment resistance. Checkpoint inhibitors and anti-HER2 agents should be investigated further in curative GEA. Abstract: Introduction: Despite multimodality treatment for curatively-treated gastroesophageal adenocarcinoma (GEA), prognosis remains dismal. The benefit of adding trastuzumab to chemotherapy for advanced Human Epidermal Growth Factor 2 (HER2) positive GEA has been established in the ToGA trial. However, it remains unclear if HER2 inhibition might also be beneficial in the curative setting. Therefore, we conducted a systematic review to investigate the role of HER2 inhibitors for the curative treatment of GEA. Methods: A systematic literature search was performed in PubMed, EMBASE, CENTRAL, and clinicaltrials.gov to identify clinical trials investigating HER2 inhibition for the curative treatment of GEA. Study quality was assessed using the GRADE methodology. Results: From the 1825 studies retrieved, 17 were included (seven published articles; three published conference abstracts; seven ongoing studies). From the published studies, eight studies investigated single-agent HER2 inhibition. Four studies had a nonrandomized design, and two were randomized controlled trials. Two published studies were assessed as high-quality. The addition of single-agent HER2 inhibition to chemo(radio)therapy showed a pathological complete response rate (pCR) of 22.2% (range, 9.6–25%) and dual HER2 inhibition of 34.5% (34–35%). Two-year disease-free survival (DFS) was 51.0% (40–71%) with single-agent and 70.0% (70–70%) with dual HER2 therapy. Discussion: Dual-agent HER2 inhibition showed promising pCR rates and DFS. Given the limited additional toxicity of the addition of HER2 targeting agents and the potential benefit of dual-targeting, further investigation is required in a phase III randomized clinical trial. Next steps include combining checkpoint inhibitors and HER2 blockade given the suggested synergism, as well as investigating new anti-HER2 agents.